Text Bond TAK ILI INACHE: Types of Constructions and Functional-Semantic Potential - N. Yu. Pilyugina; E. S. Sheremetyeva (Научный диалог, 2019)
The question of the specificity of text functions of combination tak ili inache ‘anyway’ is covered. The novelty of the study is seen in the fact that for the first time this combination is described in terms of its functioning in the text, the types of contexts characteristic of it are analyzed. The analysis revealed that the combination tak ili inache functions as means of text bond with an alternative-concessive meaning. The relevance of the study is determined by a multidimensional approach to the description of tak ili inache textual nature: this phenomenon is analyzed in terms of semantic, syntactic and communicative-pragmatic features. The characteristic of a combination tak ili inache in explanatory dictionaries and dictionaries of functional parts of speech is presented; the concept of a text bond in a circle of adjacent terms is described. It is established that the text bond tak ili inache is a formal means of organizing text constructions, structure of these constructions is described, especially the implementation of the left and right component. Special attention is paid to the explication of the communicative and pragmatic potential of the bond. On the basis of the analysis of the propositions content of the left part of structures with tak ili inache , the contextual modifications of the studied structures are distinguished. The ability of the bond to create typical text constructions characteristic of journalistic and scientific texts is noted.